Collected works (gsuṅ ʼbum) of Rgod-tshaṅ-pa Mgon-po-rdo-rje - Rgod-tshaṅ-pa Mgon-po-rdo-rje, 1189-1258 (Kunzang Tobgey, 1976)
Writings on Lamaist religious practice by the founder of the To Drukpa Kargyudpa tradition.